2005
DOI: 10.2106/jbjs.d.02645
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal-Incision Technique in Total Hip Arthroplasty Does Not Improve Early Postoperative Outcomes

Abstract: Minimally invasive total hip arthroplasty performed through a single-incision posterior approach by a high-volume hip surgeon with extensive experience in less invasive approaches to the hip is safe and reproducible. However, it offers no significant benefit in the early postoperative period compared with a standard incision of 16 cm. As it is not known whether lower-volume and less-experienced surgeons can achieve similar results, the mini-incision technique merits further study before wide dissemination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
220
3
31

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(268 citation statements)
references
References 23 publications
14
220
3
31
Order By: Relevance
“…Likewise, Berger et al reported decreased blood loss, decreased length of stay, and more rapid return to function [2][3][4][5][6][7]. However, in a randomized, controlled trial, Ogonda et al reported no difference in the theoretical advantages previously reported for MIS techniques [25]. Moreover, no difference in their length of hospital stay, noted complications involving wound healing, and acetabular component malposition contradict the theoretical shortterm results.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, Berger et al reported decreased blood loss, decreased length of stay, and more rapid return to function [2][3][4][5][6][7]. However, in a randomized, controlled trial, Ogonda et al reported no difference in the theoretical advantages previously reported for MIS techniques [25]. Moreover, no difference in their length of hospital stay, noted complications involving wound healing, and acetabular component malposition contradict the theoretical shortterm results.…”
Section: Discussionmentioning
confidence: 96%
“…The theoretical benefits of these approaches include less tissue dissection, decreased surgical blood loss, decreased postoperative pain, decreased time to hospital discharge, decreased time to the return of activities of daily living, and the potential for cost savings across the entire continuum of care [6,26]. Although MIS surgical approaches may be applied to various procedures across all disciplines of orthopaedics, and the intuitive benefits of a smaller incision length are well communicated across all public media, there still exists conflicting results in the medical literature regarding their overall benefit [10,25,30].…”
Section: Introductionmentioning
confidence: 99%
“…This might be explained by either the small patient group or by the followup time, since most beneficial effects of minimally invasive surgery are reported for the early rehabilitation period [9,24]. However, several studies suggest there are no substantial clinical benefits of minimally invasive THA [12,33,48].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, none of the approaches to the hip can be considered superior; but the trend is toward minimally invasive approaches, as it is generally accepted that muscle trauma should be reduced. However, some authors are critical of minimally invasive hip arthroplasty because of added potential risks, such as increased problems with woundhealing, implant malpositioning, additional nerve and vessel injury, and inadequate visualization during surgery [33,48]. Cadaver investigations demonstrate substantial damage to the periarticular musculature with a minimally invasive approach [27,30,34].…”
Section: Introductionmentioning
confidence: 99%
“…Proponents of minimally invasive THA cite improved patient satisfaction, less blood loss, shorter hospital stays, and early improved function [2,3,6,13,23,26]. However, in the evolution of minimally invasive THA, there has been justified concern regarding the potential for increased complications and the possibility of compromising an already very successful operative procedure [16,19,32]. Some reports of complications associated with minimally invasive THA techniques include component malposition, femoral shaft fractures, sciatic nerve palsies, femoral nerve palsy, catastrophic blood loss, significant muscle trauma, and death [1,8].…”
Section: Introductionmentioning
confidence: 99%